Developing a framework for clinical education programme for undergraduate nursing students in Ghana - Nachinab, Gilbert Ti-Enkawol (My University, 2021)
Introduction: Clinical education is an essential component of the training of nursing students. The teaching of clinical skills is faced with challenges such as a lack of formal training for preceptors, inadequate material resources and a theory-practice gap. The increase in student enrolment is a major cause of overcrowding in the classroom, skills laboratories and clinical facilities. In Ghana, there is no framework that identifies the various stakeholders in clinical education and indicates how they could work together to improve the quality of clinical education of the undergraduate nursing students. Aim: The aim of the study was to develop a framework to enable an effective clinical nursing education programme for undergraduate students. Methodology: A multimethod approach was used to conduct the study in four phases. Phase one consisted of a scoping review on the practices that facilitate clinical nursing education in the undergraduate programme. Phase two consisted of a situational analysis which was subdivided into two sections - a survey and key informant interviews. The survey was conducted among preceptors and nursing and key informant interviews were among lecturers, unit managers, nurse managers and clinical placement coordinators. Phase three involved the application lessons learnt from phase I and II in the development of the framework and implementation plan for clinical education in Ghana. The development of the framework was guided by the model for clinical education and training developed by the Nursing Educators Stakeholders Group in South Africa. Phase four was the evaluation of the implementation plan for the developed framework using a Delphi Technique. Findings: The scoping review revealed that factors that facilitate clinical nursing education were related to context, structure and process. Context-related factors that enhanced clinical nursing education include support for students, characteristics of clinical faculty and students, and academic-clinical collaboration. The structures that facilitate clinical nursing education are material resources and technology, and human resources. Processes that facilitate clinical nursing education include clinical teaching and learning, preparation and planning, communication and assessment. The survey determined preceptors’ and students’ perceptions of the clinical placement area, clinical teaching and learning, and clinical assessment. The students and preceptors all indicated there is no well resource skills laboratory, poor communicate of placed dates, and lack of clinical accompaniment. The results indicated that although the mean difference in perception among preceptors and students was statistically significant, they all indicated the need to improve clinical nursing education. The key informant interviews revealed that nursing education institutions, service settings and regulatory body all play interrelated and important roles. The key informant interviews indicated that clinical education can be enhanced through provision of resources, taking steps to enhance skills teaching in the ward and positive students’ attitude. The lessons learnt from phase one and phase two were integrated to develop a framework for clinical nursing education. An implementation plan was developed for the framework. A Delphi technique was used to evaluate the implementation plan for feasibility and relevance. Conclusion: The framework for clinical nursing education developed in the study will guide improvement of clinical education in the undergraduate nursing programme in Ghana. The developed framework highlights the need to improve communication and collaboration, clinical teaching and learning, clinical supervision, clinical placement and clinical assessment.
A thesis submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in fulfilment of the requirement for the degree of Doctor of Philosophy in Nursing, Johannesburg, 2021